Hi there! Thank you for the opportunity to help you with your question!
There is a very specific formula for the sum of cubes; when you have
a^3+b^3 = (a+b)(a^2-ab+b^2)
In this case, our "a" is actually (2x) [because (2x)^3 = 8x^3], and our "b" is actually 5 [because 5^3 = 125]
Now we just plug a and b into the formula above:
(2x)^3 + 125 = (2x+5)((2x)^2 -(2x)*5 +5^2) = (2x+5)(4x^2-10x+25)
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?